UV-Light Exposure of Insulin: Pharmaceutical Implications upon Covalent Insulin Dityrosine Dimerization and Disulphide Bond Photolysis - Correia, Manuel; Neves-Petersen, Maria Teresa; Jeppesen, Per Bendix; Gregersen, Søren; Petersen, Steffen B. (PLOS ONE, 2012)
In this work we report the effects of continuous UV-light (276 nm, ∼2.20 W.m−2) excitation of human insulin on its absorption and fluorescence properties, structure and functionality. Continuous UV-excitation of the peptide hormone in solution leads to the progressive formation of tyrosine photo-product dityrosine, formed upon tyrosine radical cross-linkage. Absorbance, fluorescence emission and excitation data confirm dityrosine formation, leading to covalent insulin dimerization. Furthermore, UV-excitation of insulin induces disulphide bridge breakage. Near- and far-UV-CD spectroscopy shows that UV-excitation of insulin induces secondary and tertiary structure losses. In native insulin, the A and B chains are held together by two disulphide bridges. Disruption of either of these bonds is likely to affect insulin’s structure. The UV-light induced structural changes impair its antibody binding capability and in vitro hormonal function. After 1.5 and 3.5 h of 276 nm excitation there is a 33.7% and 62.1% decrease in concentration of insulin recognized by guinea pig anti-insulin antibodies, respectively. Glucose uptake by human skeletal muscle cells decreases 61.7% when the cells are incubated with pre UV-illuminated insulin during 1.5 h. The observations presented in this work highlight the importance of protecting insulin and other drugs from UV-light exposure, which is of outmost relevance to the pharmaceutical industry. Several drug formulations containing insulin in hexameric, dimeric and monomeric forms can be exposed to natural and artificial UV-light during their production, packaging, storage or administration phases. We can estimate that direct long-term exposure of insulin to sunlight and common light sources for indoors lighting and UV-sterilization in industries can be sufficient to induce irreversible changes to human insulin structure. Routine fluorescence and absorption measurements in laboratory experiments may also induce changes in protein structure. Structural damage includes insulin dimerization via dityrosine cross-linking or disulphide bond disruption, which affects the hormone’s structure and bioactivity.